Polyethyleneimine-impregnated activated carbon nanofiber composited graphene-derived rice husk char for efficient post-combustion CO2capture - Che Othman, F.E. (De Gruyter Open Ltd, 2022)
This study presents the fabrication of polyethyleneimine (PEI)-graphene-derived rice husk char (GRHC)/activated carbon nanofiber (ACNF) composites via electrospinning and physical activation processes and its adsorption performance toward CO2. This study was performed by varying several parameters, including the loading of graphene, impregnated and nonimpregnated with amine, and tested on different adsorption pressures and temperatures. The resultant ACNF composite with 1 of GRHC shows smaller average fiber diameter (238 ± 79.97 nm) with specific surface area (S BET) of 597 m2/g, and V micro of 0.2606 cm3/g, superior to pristine ACNFs (202 m2/g and 0.0976 cm3/g, respectively). ACNF/GRHC0.01 exhibited CO2 uptakes of 142 cm3/g at atmospheric pressure and 25°C, significantly higher than that of pristine ACNF's 69 cm3/g. The GRHC/ACNF0.01 was then impregnated with PEI and further achieved impressive increment in CO2 uptake to 191 cm3/g. Notably, the adsorption performance of CO2 is directly proportional to the pressure increment; however, it is inversely proportional with the increased temperature. Interestingly, both amine-impregnated and nonimpregnated GRHC/ACNFs fitted the pseudo first-order kinetic model (physisorption) at 1 bar; however, best fitted the pseudo second-order kinetic model (chemisorption) at 15 bar. Both GRHC/ACNF and PEI-GRHC/ACNF samples obeyed the Langmuir adsorption isotherm model, which indicates monolayer adsorption. At the end of this study, PEI-GRHC/ACNFs with excellent CO2 adsorption performance were successfully fabricated. © 2022 Faten Ermala Che Othman et al., published by De Gruyter.